2019
DOI: 10.1111/avsc.12433
|View full text |Cite
|
Sign up to set email alerts
|

Environment or management? Relative importance for floristic composition of sub‐Mediterranean hay meadows in Central Italy

Abstract: Questions:What are the separate and combined effects of natural and management factors on floristic assemblage in sub-Mediterranean hay meadows? How are hay meadow dynamics affected by the environment excluding management?Location: Central Apennines, Italy.Methods: Vegetation was studied in 66 hay meadows by random plots, recording four groups of explanatory variables: management, soil, topography, and space. Using partial ordinations, the explanatory variables of the variation in floristic composition and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The vegetation of the study area is mowed once a year, usually at the end of July, and only occasionally it is grazed by a few animals after mowing. For details on management and its implications on flora composition, see Giallonardo et al (2019).…”
Section: Study Areamentioning
confidence: 99%
“…The vegetation of the study area is mowed once a year, usually at the end of July, and only occasionally it is grazed by a few animals after mowing. For details on management and its implications on flora composition, see Giallonardo et al (2019).…”
Section: Study Areamentioning
confidence: 99%
“…Investigating the influence of different sets of variables on biotic communities is crucial to understand community variation across time and space, and to define conservation strategies (Maccherini et al 2011;Barbato et al 2019;Giallonardo et al 2019;Hu et al 2022). Environmental and geographic features are pivotal for the survival of arable plant species (Walker et al 2007;Fanfarillo et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Species distribution along environmental gradients reflects the effects of several factors at different scales (Givnish, 1999). At present, ecologists have abandoned the notion that community organization is driven by a single monolithic factor, and most reviews on this topic concluded that multiple processes must be invoked in order to explain community organization (Dunson & Travis, 1991); moreover, some authors emphasize the role played by management or environmental variables (Giallonardo et al, 2019) or the spatial factor (spatial distribution of samples) in combination with environmental variables to explain changes in the composition of communities (Bauman et al, 2019;Truchy et al, 2019). At a global perspective about arid environments, vegetation types coincide with the pattern of the water resources of the habitat, not only the water resources of a particular habitat that are controlled by the local topography, also the physical and chemical attributes of the soil are important for it (Abd El-Ghani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%